Ketidakefektifan Kalimat dalam Surat Pembaca Bali Post Periode Januari--Agustus 2020-converted - Khusnika, Riza Milinia Vrindi; Suparwa, I Nyoman (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p14, 2021)
This article is entitled "The Ineffectiveness of Sentences in Bali Post Readers' Letter for the January - August 2020 Period". The topic selection was based on the ineffective sentence problems found in the Bali Post readers' letters. Ineffective sentences must be avoided so that the process of conveying and receiving information is perfect. The problem is focused on two things. First, the ineffectiveness of the Bali Post sentences for the period January - August 2020. Second, the factors causing the ineffectiveness of the sentence. The theory used is Keraf (1980), Verhaar (1982), Razak (1986), Putrayasa (2010), and Widjono (2012). The method used is descriptive analytic. The data were selected based on purposive sampling technique. The results showed that there were sentence ineffectiveness in the Bali Post 2020 readership letter, such as structural errors, sentence confusion, diction errors, and spelling errors. The ineffectiveness of sentences is caused by several factors, namely the presence of contamination or confusion, pleonasm, ambiguity, ambiguity of sentence elements, redundant prepositions, errors of reasoning, inaccuracy of word forms, inaccurate meanings of words, the influence of foreign languages, and the influence of regional languages.